Development of novel reduced graphene oxide/metalloporphyrin nanocomposite with photocatalytic and antimicrobial activity for potential wastewater treatment and medical applications - Ahmed M. El-Khawaga; Hesham Tantawy; Mohamed A. Elsayed; Ahmed I. A. Abd El-Mageed (Scientific Reports, 2024)
Abstract This research investigates a novel nanocomposite material composed of reduced graphene oxide (rGO) and nickel-5,15-bisdodecylporphyrin (Ni-BDP) nanoparticles for the effective removal of methyl orange (MO), a harmful synthetic dye, from water. The structure and composition of the synthesized rGO/Ni-BDP nanocomposite were characterized using high-resolution transmission electron microscopy (HR-TEM), Raman spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry, and ultraviolet-visible (UV-Vis) spectroscopy. The study demonstrates the material’s efficacy as both a catalyst and adsorbent for MO removal. Optimal performance was observed at pH 3.0, where the positively charged nanocomposite surface facilitated strong interactions with negatively charged MO molecules, leading to enhanced photocatalytic activity. Under these conditions, 0.01 g of the nanocomposite achieved an impressive 86.2% MO removal efficiency. Furthermore, the study explored the reusability of the rGO/Ni-BDP nanocomposite in repeated cycles of photocatalytic MO degradation under visible light irradiation. While exhibiting some decrease in efficiency over five cycles, the nanocomposite maintained a respectable degradation rate even after multiple uses. Finally, the antimicrobial properties of the nanocomposite were evaluated against both Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria exhibiting a zone of inhibition measuring 23 mm and 26, respectively. The minimum inhibitory concentration (MIC) values of 2.50 µg/ml and 1.25 µg/ml for Escherichia coli and Staphylococcus aureus, respectively. The results revealed significant antibacterial activity, demonstrating the broad-spectrum efficacy of the rGO/Ni-BDP nanocomposite. This research underscores the potential of the rGO/Ni-BDP nanocomposite as a versatile material for environmental remediation and antibacterial applications.